The RELATIONSHIP BETWEEN FILM SEQUELS AND TICKET & MERCHANDISE PURCHASE DECISIONS FOR SPIDER-MAN: NO WAY HOME WITH CONSUMER SATISFACTION AS AN INTERVENING VARIABLE - Muhammad Alkubbarul Hafiz; Ekasari, Novita; Hasbullah, Husni (Journal of Business Studies and Management Review, 2025)
The film industry has experienced rapid growth in recent decades, with sequels playing a crucial role in maintaining audience engagement and increasing revenue. Spider-Man: No Way Home serves as an example of a successful sequel that attracted millions of viewers and generated substantial merchandise sales. However, not all sequels achieve the same level of success, leading to questions about the factors influencing audience decisions. This study aims to analyze the impact of film sequels on ticket and merchandise purchase decisions, with consumer satisfaction as an intervening variable. A quantitative research approach was employed, utilizing a survey method to collect data from fans of Spider-Man: No Way Home in Indonesia. The data were analyzed using Structural Equation Modeling (SEM). The findings indicate that film sequels significantly influence purchase decisions, both directly and through consumer satisfaction. The study confirms that satisfaction with a previous film strongly impacts a viewer’s decision to watch the sequel and purchase related merchandise. These results provide valuable insights for the film industry in designing more effective marketing strategies, particularly in ensuring high-quality storytelling and audience engagement to sustain franchise success. The study also highlights the importance of consumer loyalty, suggesting that maintaining a positive audience experience is key to long-term profitability in the entertainment industry